Medial sural artery perforator free flap for small- to medium-sized defects in head and neck reconstruction: a suitable replacement for radial forearm free flap - Yulian Zhang; Keran Pan; Jian Wu; Xi Tang (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background and objectives To compare clinical outcomes and donor site morbidity between medial sural artery perforator (MSAP) flap and radial forearm free (RFF) flap for soft tissue reconstruction of head and neck. Methods Forty-six patients who underwent free flap reconstruction at the head and neck cancer center from February 2019 to March 2021 were included, of which 25 RFF flaps and 21 MSAP flaps. The patient and flap characteristics (age, sex, flap size, harvest time, etc.) and outcomes (success rate, donor site complications including infection, hematoma, and fistula, donor site morbidity including abnormal sensation, weakness, range of motion, postoperative oral function) were recorded and compared. Patients were followed up for at least 12 months after surgery. The patients were assessed subjective donor-site morbidity and satisfaction with overall functional results using a self-reported questionnaire. Results The success rates of RFF flaps and MSAP flaps were 96% and 95.2%. There were no significant differences in age, sex, flap size, pedicle length, postoperative treatment, and postoperative oral function. MSAP flap showed less donor site morbidity and better subjective satisfaction at the donor site than RFF flap did after a 12-month follow-up. A dominant perforator of the medial sural artery emerges constantly near the point which is approximately 15 cm from the popliteal fossa center vertically, and 3 cm from the postor midline of the leg horizontally. Conclusion Due to less donor site morbidity and higher patient satisfaction, MSAP flap can be used as a replacement for RFF flap for small to medium-sized defects in head and neck reconstruction.